Classificação e resolução de defeitos em manutenção de software utilizando ODC e histórico de soluções - Manhães, Marcelo Mota (2014)
Nowadays with the increasing of demand in support services such as high availability and performance faced by customers and low cost operations to software maintenance and hosting enterprises, the resolution of software incidents in less time and defect prevention turned a key point. Moreover, the software maintenance is one most time consuming and effort demanding and by consequence cost in software development life cycle. Balancing effectiveness and costs turn a challenge to any enterprise that manages support in software maintenance. The approach used on this research defines a process to classify defects and boundary a set of best solutions associated to these classes from defects history and customer knowledge base. Also this classification separates different problem complexities that can be handled to different support teams. The base method used is the ODC (Orthogonal Defect Classification). With this research is possible to verify that the classification and solutions associations with problem class can undertake a time reduction in incidents resolution in software maintenance. It was verified using four service provider samples in two different customers (X and Y) that classification of defects, correct support team redirection and best solution grouping helps on reduction of incidents resolution time between 70% of incidents to customer Y and 92,5 % of incidents to customer X. The reduction was reached with reduction in number of transfers between supporting teams and incidents number reduction. The process is incremental because it is unfolded from history information and from effectiveness into solutions purposed. This process can leverage human resources nedded to support computational systems in service providers.